Achieving nitritation in a continuous moving bed biofilm reactor at different temperatures through ratio control. (February 2017) - Bian, Wei; Zhang, Shuyan; Zhang, Yanzhuo; Li, Wenjing; Kan, Ruizhe; Wang, Wenxiao; Zheng, Zhaoming; Li, Jun
Highlights: A ratio control strategy was used to remain stable nitritation in MBBR. Oxygen-limiting conditions in biofilm reactor were determined in this study. Nitritation was recovered in low temperature of 6 °C through ratio control. Stable nitritation was achieved without complete wash-out of NOB. Choice of partial or full nitritation was recommended. Abstract: A ratio control strategy was implemented in a continuous moving bed biofilm reactor (MBBR) to investigate the response to different temperatures. The control strategy was designed to maintain a constant ratio between dissolved oxygen (DO) and total ammonia nitrogen (TAN) concentrations. The results revealed that a stable nitritation in a biofilm reactor could be achieved via ratio control, which compensated the negative influence of low temperatures by stronger oxygen-limiting conditions. Even with a temperature as low as 6 °C, stable nitritation could be achieved when the controlling ratio did not exceed 0.17. Oxygen-limiting conditions in the biofilm reactor were determined by the DO/TAN concentrations ratio, instead of the mere DO concentration. This ratio control strategy allowed the achievement of stable nitritation without complete wash-out of NOB from the reactor. Through the ratio control strategy full nitritation of sidestream wastewater was allowed; however, for mainstream wastewater, only partial nitritation was recommended.